Revision of the genus Opisthozemius Kolbe, 1916, with description of a new species and designation of a new genus (Coleoptera: Brentidae, Cyphagoginae) - Orbach, Eylon; Bartolozzi, Luca (Fragmenta entomologica, 2019)
The Afrotropical genus Opisthozemius Kolbe, 1916 is revised. The genus now includes four species, one of which is described as new: Opisthozemius naamae sp. nov., from Tanzania and Zambia. Opisthozemius sulcithorax Damoiseau, 1967, from Java, is removed from the genus Opisthozemius and included in Euparagogus gen. nov. Opisthozemius honestus is placed in synonymy with Opisthozemius vittatus (new synonymy). A key for the identification of the species of Opisthozemius and some distributional data are also given. O. appendiculatus is quoted for the first time from Ghana; O. vittatus for the first time from Central African Republic, Ghana and Uganda.